Health justice for all : the development of alternative health system capabilities in the conflict-affected context of Shan State, Myanmar : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Development Studies at Massey University, Manawatū, New Zealand - Bell, Sharon Margaret (Massey University, 2018)
As the 2030 Agenda for Sustainable Development advances, it is vital to determine how conflict impacts on the achievement of the Sustainable Development Goals (SDGs) in conflict-affected contexts. The United Nations (UN) regards conflict as the leading risk to development progress as these contexts have high rates of poverty and limited access to crucial healthcare services. Shan State, Myanmar is one such context, facing a critical shortage in its health workforce, considered one of the building blocks of an effective health system. Approaches to building health workforce capabilities can meaningfully contribute towards meeting SDG 3 – ‘to ensure healthy lives and promote well-being for all at all ages’, and consequently, health justice for conflict-affected communities. This research aims to understand how the approaches taken by an international nongovernmental organisation (INGO) support the development of alternative health system capabilities in a conflict-affected context. A global development agenda of state- and peace-building has meant that INGOs have been criticised for undermining state legitimacy. Meanwhile, non-state armed groups (NSAGs) in areas like Shan State, Myanmar, have established alternative regimes which seek self-determination as well as attempting to provide for the social and economic wellbeing of their people. However, little is known about how a partnership between an INGO and a NSAG contributes toward enabling alternative health system development in these contexts. This research contributes to new ways of understanding this through the development of a capabilities framework for health system development in conflict-affected contexts. This was used to analyse findings from the qualitative case study of an INGO’s health workforce training programme on the Myanmar-Thailand border. The research found that a positive partnership between the INGO and the NSAG has played a crucial role in enabling the workforce capabilities of the alternative health system, leading to promising improvements in health outcomes in communities. However, the effectiveness of the programme is restricted by the INGO’s reliance on volunteerism for staffing, where expatriate medical volunteers are selected based on their availability, rather than the appropriate skills and experience for this context. The international aid community has also reduced its funding for cross-border development programmes in Myanmar which has constrained the activities of the INGO and the NSAG. For Myanmar to achieve health justice and SDG 3, supporting health system development that focuses on improving health outcomes needs to be a priority for the international community.
Keywords: Public health; Medical care; International cooperation; Non-governmental organizations; Shan State; Burma; Myanmar; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Health and medical services in society